The double burden of disease and the challenge of health access: Evidence from access, bottlenecks, cost and equity facility survey in Ghana - Kushitor, M.K.; Boatemaa, S. (PLoS ONE, 2018)
Despite the double burden of infectious and chronic non-communicable diseases in Africa, health care expenditure disproportionately favours infectious diseases. In this paper, we examine quantitatively the extent of this disproportionate access to diagnoses and treatment of diabetes, hypertension and malaria in Ghana. A total of 220 health facilities was surveyed across the country in 2011. Findings indicate that diagnoses and treatment of infectious diseases were more accessible than NCDs. In terms of treatment, 78% and 87% of health facilities had two of the recommended malaria drugs while less than 35% had essential diabetes and hypertension drugs. There is a significant unmet need for diagnoses and treatment of NCDs in Ghana. These inequities have implications for high morbidity and mortality from NCDs. We recommend the use of task shifting as a model to increase the delivery of NCD services.
Keywords: Health access; chronic non-communicable diseases; Africa; Health care; Hypertension